Inactivation of the β(1,2)-xylosyltransferase and the α(1,3)-fucosyltransferase genes in Nicotiana tabacum BY-2 Cells by a Multiplex CRISPR/Cas9 Strategy Results in Glycoproteins without Plant-Specific Glycans - Mercx, Sébastien; Smargiasso, Nicolas; Chaumont, François; De Pauw, Edwin; Boutry, Marc; Navarre, Catherine (Frontiers in Plant Science, 2017)
Plants or plant cells can be used to produce pharmacological glycoproteins such as antibodies or vaccines. However these proteins carry N-glycans with plant-typical residues [β(1,2)-xylose and core α(1,3)-fucose], which can greatly impact the immunogenicity, allergenicity, or activity of the protein. Two enzymes are responsible for the addition of plant-specific glycans: β(1,2)-xylosyltransferase (XylT) and α(1,3)-fucosyltransferase (FucT). Our aim consisted of knocking-out two XylT genes and four FucT genes (12 alleles altogether) in Nicotiana tabacum BY-2 suspension cells using CRISPR/Cas9. Three XylT and six FucT sgRNAs were designed to target conserved regions. After transformation of N. tabacum BY-2 cells with genes coding for sgRNAs, Cas9, and a selectable marker (bar), transgenic lines were obtained and their extracellular as well as intracellular protein complements were analyzed by Western blotting using antibodies recognizing β(1,2)-xylose and α(1,3)-fucose. Three lines showed a strong reduction of β(1,2)-xylose and α(1,3)-fucose, while two lines were completely devoid of them, indicating complete gene inactivation. The absence of these carbohydrates was confirmed by mass spectrometry analysis of the extracellular proteins. PCR amplification and sequencing of the targeted region indicated small INDEL and/or deletions between the target sites. The KO lines did not show any particular morphology and grew as the wild-type. One KO line was transformed with genes encoding a human IgG2 antibody. The IgG2 expression level was as high as in a control transformant which had not been glycoengineered. The IgG glycosylation profile determined by mass spectrometry confirmed that no β(1,2)-xylose or α(1,3)-fucose were present on the glycosylation moiety and that the dominant glycoform was the GnGn structure. These data represent an important step toward humanizing the glycosylation of pharmacological proteins expressed in N. tabacum BY-2 cells.